Fertility Treatments in Women Who Become Pregnant and Carried to Viability, and the Risk for Long-Term Maternal Cardiovascular Morbidity - Ben-Yaakov, R. Djaoui; Kessous, R.; Shoham-Vardi, I.; Sergienko, R.; Pariente, G.; Sheiner, E. (American Journal of Perinatology, 2016)
Objective The objective of this study was to investigate whether patients who undergo fertility treatments (ovulation induction or in vitro fertilization) have an increased risk for future maternal cardiovascular morbidity.Design A population-based study compared the incidence of long-term cardiovascular morbidity in a cohort of women with and without a previous exposure to fertility treatments. Deliveries occurred during a 25-year period, with a mean follow-up of 11.7 years. Women with known cardiovascular disease and congenital cardiovascular malformations diagnosed before the index pregnancy and multiple pregnancies were excluded.Results During the study period, 99,291 patients met the inclusion criteria; 4.1% (n = 4,153) occurred in patients with exposure to fertility treatments. Patients with exposure to fertility treatments did not have higher rates of cardiovascular morbidity. Using a Kaplan–Meier survival curve, patients with an exposure to fertility treatments had no higher cumulative incidence of cardiovascular hospitalizations. Using a Cox proportional hazards model, adjusted for confounders such as preeclampsia, diabetes mellitus, and obesity, exposure to fertility treatments remained unassociated with cardiovascular hospitalizations (adjusted hazard ratio = 1.1; 95% confidence interval, 0.9–1.3; p = 0.441).Conclusion In our population, during a mean follow-up period of 11.7, results showed no increased risk for cardiovascular morbidity in women undergoing fertility treatments.
Keywords: fertility treatments; in vitro fertilization; ovulation induction; cardiovascular morbidity